PENGARUH PICE DISCOUNT, PRODUCT QUALITY DAN ENDORSMEN TERHADAP LOYALITAS KONSUMEN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO AMANDA BROWNIS SITUBONDO - Syarif Hidayatullah; Ediyanto Ediyanto; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study was to determine the effect of price discounts, product quality, and endorsements on consumer loyalty through purchase intention as an intervening variable at the Amanda Brownies Store in Situbondo. The sampling technique used in this study was probability sampling with 98 respondents. Data analysis used structural equation analysis with the assistance of smart PLS 3.0 software. The results of the study indicate that price discounts have a positive but insignificant effect on consumer loyalty. Product quality has a positive and significant effect on consumer loyalty. Endorsements have a negative but insignificant effect on consumer loyalty. Price discounts have a positive but insignificant effect on purchase intention. Product quality has a positive and significant effect on purchase intention. Endorsements have a negative but insignificant effect on purchase intention. Consumer loyalty has a positive but insignificant effect on purchase intention.